2013
DOI: 10.1021/mp4000794
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Engineering of Green Tea Epigallocatechin-3-gallate (EGCg) Cocrystals and Pharmacokinetic Modulation in Rats

Abstract: The most abundant polyphenol in green tea, epigallocatechin-3-gallate (EGCg), has recently received considerable attention due to the discovery of numerous health-promoting bioactivities. Despite reports of its poor oral bioavailability, EGCg has been included in many dietary supplement formulations. Conventional preformulation methods have been employed to improve the bioavailability of EGCg. However, these methods have limitations that hinder the development of EGCg as an effective therapeutic agent. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 54 publications
3
67
0
Order By: Relevance
“…improving key physicochemical properties such as physical stability, 51,64,87,88,92,97,146 solubility 61,62,87,88,96,112 and bioavailability 96,112 of nutraceuticals, as well as of APIs. A summary of these studies is provided in Tables 4-5 and case studies discussed in more detail below.…”
Section: Tuning Physicochemical Propertiesmentioning
confidence: 99%
“…improving key physicochemical properties such as physical stability, 51,64,87,88,92,97,146 solubility 61,62,87,88,96,112 and bioavailability 96,112 of nutraceuticals, as well as of APIs. A summary of these studies is provided in Tables 4-5 and case studies discussed in more detail below.…”
Section: Tuning Physicochemical Propertiesmentioning
confidence: 99%
“…Different gavage vehicles are known produce PK changes for orally administered APIs. 46 Formulation can also drastically impact the oral PK of cocrystals and a recent study revealed that dosing of unformulated cocrystals might result in a perceived failure to produce accurate PK modulation. 9c 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 CrystEngComm.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] The supramolecular synthon approach where complementary functional groups pair up is key in the design of new crystal structures. [4][5][6] In particular the sythons involving carboxylic acid and nitrogen-containing functionalities have received much attention.…”
Section: Introductionmentioning
confidence: 99%